ASSESSING STUDENT LEADERSHIP CONTRIBUTION TOWARDS THE ATTAINMENT OF UNIVERSITY GOALS IN CRISIS PERIOD IN THE NORTH WEST REGION OF CAMEROON - Ngwa, Emmanuel Shu (Journal of Higher Education and Academic Advancement, 2025)
Objective: Since 2016, public, private and confessional owned Universities within Bamenda, the Metropolitan capital of the North West Region of Cameroon have struggled to sustain their tri-function mission of teaching, research and community outreach; amidst a raging conflict – the Anglophone crisis, where education stakeholders and education infrastructure have been targeted. Given the critical place of student leaders in university governance sustainability; this study therefore assessed student leadership contribution in aiding the attainment of university goals and objectives within the conflict period. Key focus was on three dimensions: communication strategies, student mobilization efforts, and advocacy for student interests. Method: Using a mixed concurrent nested research design, data was collected from university students, student leaders and University administrators using a structured questionnaire administered to 278 final year undergraduate and postgraduate students from three selected universities, along with in-depth interviews with 7 student leaders and 3 university administrators. Simple descriptive statistics of frequency counts and percentages, and thematic analyses were used to analyze data from the questionnaire and interviews respectively. Results: The findings revealed that student leaders generally employed an effective communication strategy (67.6% approval as against 32.4%), with social media being critical in their strategy. Student leaders’ mobilization strategy was rated as positive (70% as against 30%). Advocacy for students’ interest received a relatively positive rating (63.4% as against 36.6%). Novelty: The study notes that while student leaders have played a critical role in facilitating university functioning during the conflict period; there are however opportunities for enhancement in bidirectional communication, inclusive student mobilization, and translating advocacy into concrete policy changes. Recommendations include implementing structured feedback mechanisms, developing targeted engagement strategies for underrepresented students on campuses, and strengthening collaborative approaches with university administration to increase the effectiveness of advocacy efforts.